PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, PELAYANAN FISKUS, SANKSI PERPAJAKAN DAN PERSEPSI EFEKTIFITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Wahyudi, Djoko; Nur Izza Nafi’ah, 15.05.62.0024 (Students' Journal of Accounting and Banking, 2018)
The purpose of this study is to analyze the influence of knowledge of tax regulations, taxpayer’s awareness, tax authorities service, taxation sanction, perception of the tax system’s effectiveness of the tax system on the compliance of individual taxpayers who have a business in the Kudus district. The population in this study is an individual UMKM taxpayer registered at KPP Pratama Kudus. The sample in this study were 113 people, with the sampling technique using the method simple random sampling. The results showed that influence of knowledge of tax regulations, taxpayer’s awareness, tax authorities service, taxation sanction, perception of the tax system’s effectiveness has a positive effect on taxpayer’s compliance. Keywords: knowledge of tax regulations, taxpayer’s awareness, tax authorities service, taxation sanction, perception of the tax system’s effectiveness, taxpayer’s compliance.